1988
DOI: 10.1111/j.1471-4159.1988.tb03056.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfoglucuronyl Neolactoglycolipids in Adult Cerebellum: Specific Absence in Murine Mutants with Purkinje Cell Abnormality

Abstract: It is shown here that glycolipids of the sulfoglucuronyl neolacto series (SGGLs) are present in the adult rodent cerebellum. SGGLs were not detected in the cerebellar murine mutants lurcher, Purkinje cell degeneration, and staggerer, in which Purkinje cell loss is the primary defect. SGGLs were present, however, in normal amounts in weaver and reeler mutants, in which there is a major and relatively specific loss of granule cells without obvious deficiency in Purkinje cells. In the myelin-deficient quaking mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Other cell types do not have this enzyme activity. Deficiency of GlcNAc-Tr in the Purkinje cell abnormality mutants would explain severe reduction of all neolactoglycolipids derived from LcOse 3 Cer in the mutants (1,(27)(28)(29). Although levels of LcOse 3 Cer were not measured in the mutants' cerebella, analysis of its immediate product nLcOse 4 Cer showed that it was only 4, Ͻ1, and 2.6% of the normal (ϳ3 ng/mg dry weight) in Lc/ϩ, tg la /tg la , and pcd/pcd mutants, respectively (27,29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other cell types do not have this enzyme activity. Deficiency of GlcNAc-Tr in the Purkinje cell abnormality mutants would explain severe reduction of all neolactoglycolipids derived from LcOse 3 Cer in the mutants (1,(27)(28)(29). Although levels of LcOse 3 Cer were not measured in the mutants' cerebella, analysis of its immediate product nLcOse 4 Cer showed that it was only 4, Ͻ1, and 2.6% of the normal (ϳ3 ng/mg dry weight) in Lc/ϩ, tg la /tg la , and pcd/pcd mutants, respectively (27,29).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of SGGLs and other glycolipids derived from LcOse 3 Cer such as, lactoneotetraosylceramide, lactoneohexaosylceramide, Le x antigens, and ganglioside nLD1, in these mutants was specific, since other lipids were not affected significantly. The expression of SGGLs was essentially normal in other cerebellar mutants, such as weaver, reeler, and quaking, where cells other than Purkinje cells are primarily affected (27)(28)(29).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…In the adult rat cerebellum, the expression of SGGLs is kept constant (16,17). Immunohistochemical studies localized SGGLs in specific cells during the development of the cerebellum, and suggested some biological functions for neuron guidance (14,15,17,18). In rat cerebral cortex, the expression of SGGLs peaked at embryonic day (ED) 19 and then decreased until postnatal PD 5, and had almost completely disappeared by PD 20. Carbohydrate chains on SGGLs are extended by stepwise reactions catalyzed by glycosyltransferases.…”
mentioning
confidence: 99%